Stress shielding following stemless anatomic total shoulder arthroplasty. (February 2023) - Aibinder, William R; Uddin, Fares; Bicknell, Ryan T; Krupp, Ryan; Scheibel, Markus; Athwal, George S
Background: Finite element analysis has suggested that stemless implants may theoretically decrease stress shielding. The purpose of this study was to assess the radiographic proximal humeral bone adaptations seen following stemless anatomic total shoulder arthroplasty. Methods: A retrospective review of 152 prospectively followed stemless total shoulder arthroplasty utilizing a single implant design was performed. Anteroposterior and lateral radiographs were reviewed at standard time points. Stress shielding was graded as mild, moderate, and severe. The effect of stress shielding on clinical and functional outcomes was assessed. Also, the influence of subscapularis management on the occurrence of stress shielding was determined. Results: At 2 years postoperatively, stress shielding was noted in 61 (41%) shoulders. A total of 11 (7%) shoulders demonstrated severe stress shielding with 6 occurring along the medial calcar. There was one instance of greater tuberosity resorption. At the final follow-up, no humeral implants were radiographically loose or migrated. There was no statistically significant difference in clinical and functional outcomes between shoulders with and without stress shielding. Patients undergoing a lesser tuberosity osteotomy had lower rates of stress shielding, which was statistically significant ( p = 0.021) Discussion: Stress shielding does occur at higher rates than anticipated following stemless total shoulder arthroplasty, but was not associated with implant migration or failure at 2 years follow-up. Level of evidence: IV, Case series.